Impossible monsters : dinosaurs, Darwin, and the battle between science and religion - Taylor, Michael (Michael Hugh), 1988- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2024)
"When the twelve-year-old daughter of a British carpenter pulled some strange-looking bones from the country's southern shoreline in 1811, few people dared to question that the Bible told the accurate history of the world. But Mary Anning had in fact discovered the 'first' ichthyosaur, and over the next seventy-five years--as the science of paleontology developed, as Charles Darwin posited radical new theories of evolutionary biology, and as scholars began to identify the internal inconsistencies of the Scriptures--everything changed. Beginning with the archbishop who dated the creation of the world to 6 p.m. on October 22, 4004 BC, and told through the lives of the nineteenth-century men and women who found and argued about these seemingly impossible, history-rewriting fossils, Impossible Monsters reveals the central role of dinosaurs and their discovery in toppling traditional religious authority, and in changing perceptions about the Bible, history, and mankind's place in the world"--